World Bank-Civil Society Engagement : Review of Fiscal Years 2005 and 2006 - World Bank (World Bank, Washington, DC, 2018)
Fiscal Year 2005 and 2006 have confirmed a growing trend in Bank-civil society relations: more substantive policy dialogue at the global level, and greater country-level operational collaboration. Not only is the policy dialogue around complex and sensitive issues at the global level becoming more fluid, but the PRS process continues to open up important policy space for government-civil society engagement at the country level. On the operational level, as the joint tsunami reconstruction efforts in Asia are demonstrating, civil society and governments can be complementary partners in the development process. Yet as the Bank’s own Issues and Options paper and various CSO critiques have confirmed, the Bank faces many challenges in order to realize the greater opportunities that Bank-civil society dialogue and collaboration have to offer. The Bank must improve its own mechanisms for civil society engagement and accountability; ensure that best practices are applied more consistently across the institution; and encourage member governments to improve the enabling environment for civil society to flourish in their countries.